The Effect of Plant Density on Yield and Quality of Garden Cress (Lepidium sativum L.) - Dilek Yılmaz; Atnan Uğur (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in greenhouse and laboratories of Department of Horticulture (Faculty of Agriculture, Ordu University, Ordu, Turkey) in 2013-2014 production seasons in Ordu ecological condition. Commercial garden cress standard seeds were used as plant materials. Plant densities were calculated upon the seed quantity spread on 1 m2, and seeds were sown for 1.0, 1.5, 2.0 and 2.5 g per m2. Peat: perlite mix prepared in proportion of 3:1 was used as the growing medium and filled in 50×16×14 cm sized plastic pots. The garden cress plants were harvested on the 45th day after seeding. The yield, leaf petiole length, leaf length, leaf width and chlorophyll content of the harvested plants were determined. It has been determined that quality parameters vary depending on plant density and varieties. The highest plant yield was obtained from “BT Bu-ter” garden cress variety with 2.489.2 g/m2. The plant yield in different plant densities was increased in the rates varying between 3.31% and 8.25%. The increasing plant densities caused an increase in yield but negatively affected the leaf quality in terms of both length and chlorophyll content. Leaf width, leaf length, leaf petiole length and chlorophyll content were decreased depending on the increase in plant densities. Based on the information obtained, it was considered useful to choose a plant densities based on the variety and growing season according to the growing purpose.